Determination of the Boundary Well Consolidation Limit for the Final Operation of the Reservoir - Bobomurodov Utkir Ziyadullaevich (Scientific Trends, 2024)
The imperial concernings used to identify the net law are as follows. The results of drilling well drilling were evaluated at different periods of operation of the Shurtepa deposit. It was determined that the wells were to be tightened and that each well would be reduced to the specific oil reserves.
Keywords: Mining, alignment, well, traction, netting, compression, removable backup, coverage, dynamics, evaluation, effectiveness.